2021
DOI: 10.1371/journal.pgen.1009792
|View full text |Cite
|
Sign up to set email alerts
|

Conditional knockdown of transformer in sheep blow fly suggests a role in repression of dosage compensation and potential for population suppression

Abstract: The transformer (tra) gene is essential for female development in many insect species, including the Australian sheep blow fly, Lucilia cuprina. Sex-specific tra RNA splicing is controlled by Sex lethal (Sxl) in Drosophila melanogaster but is auto-regulated in L. cuprina. Sxl also represses X chromosome dosage compensation in female D. melanogaster. We have developed conditional Lctra RNAi knockdown strains using the tet-off system. Four strains did not produce females on diet without tetracycline and could po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 56 publications
(127 reference statements)
0
2
0
Order By: Relevance
“…More and more examples show that the sex‐specific lethality genes of the sex‐determination pathway not only function in sex determination, but also in X chromosome dosage compensation. In D. melanogaster and A. gambiae , sex‐specific lethality caused by loss‐of‐function mutations or knockdown of sex‐determination genes results from misregulation of dosage compensation 17,33–35 . We found that RNAi‐mediated knockdown of the expression of Rpfmd caused the female‐specific lethality.…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…More and more examples show that the sex‐specific lethality genes of the sex‐determination pathway not only function in sex determination, but also in X chromosome dosage compensation. In D. melanogaster and A. gambiae , sex‐specific lethality caused by loss‐of‐function mutations or knockdown of sex‐determination genes results from misregulation of dosage compensation 17,33–35 . We found that RNAi‐mediated knockdown of the expression of Rpfmd caused the female‐specific lethality.…”
Section: Resultsmentioning
confidence: 82%
“…In D. melanogaster and A. gambiae, sex-specific lethality caused by loss-of-function mutations or knockdown of sexdetermination genes results from misregulation of dosage compensation. 17,[33][34][35] We found that RNAi-mediated knockdown of the expression of Rpfmd caused the female-specific lethality. We therefore compared the autosomes and X chromosomes transcription of dsRpfmd female with that of dsgfp females, and found that X chromosome transcription in dsRpfmd females was significantly up-regulated, which in other species, was toxic and might cause the female-specific death, indicating that Rpfmd regulated the dosage compensation in R. pedestris (Fig.…”
Section: The Targets Of Rpfmd In R Pedestrismentioning
confidence: 90%